Pengaruh Pemberian Variasi Dosis Pupuk Kandang Terhadap Pertumbuhan Tanaman Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) - Nur Anggraeni, Dewi (Biogenesis: Jurnal Ilmiah Biologi, 2014)
Research on the effect of dose variations of manure on God’s Crown (Phaleria macrocarpa (Scheff.) Boerl.) growth was implemented in Ambarketawang, Gamping, Sleman, Yogyakarta. This study aimed to determine the effect of administration of dose variations of manure on God’s Crown growth. This research method using a complete randomized design (CRD) with one treatment factors which is administrating manure into polybags containing 2 kg of soil with dose variations of 0 g, 50 g, 100 g, 150 g, 200 g, and 250 g. The parameters measured in this study are height, leaf number, and fresh weight of Crown’s God plant. The results were analyzed by analysis of variance (ANOVA), ifthe data is meaningful (significant difference) then followed by LSD test level of 5%. The results obtained are the effects of administration of manure dose variation produce different Crown’s God (Phaleria macrocarpa (Scheff.) Boerl.) growth, and the best dose for Crown’s God (Phaleria macrocarpa (Scheff.) Boerl .) growth is 250 grams.Keywords: crown’s god (Phaleria macrocarpa (Scheff.) Boerl.), dose of manure